Getting the most out of attending aesthetic conferences. (2nd March 2023) - Bird, Vanessa
Abstract : This article will share effective tips on how to get the most out of attending an aesthetic conference to maximise professional and personal growth. From shortlisting what conferences to go to, to the logistics of your trip and whether you want to go with a conference 'buddy', the work starts long before you step through the doors of the conference centre. You may already plan what lectures and demonstrations to attend based on your future business and educational goals, but are you making the most of the exhibition, meeting with distributors and networking with your peers? Have you prioritised what you want to get out of attending each conference and do you always review what you learned post-event? This guide will help you focus your time and attention, ensuring your conference days off-site from your clinic leads to business, personal and financial growth.